Analisis Kesalahan Berbahasa Indonesia pada Kegiatan Story Telling Mahasiswa Universitas Terbuka Kefamenanu - Siki, Ferdinandus (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This article discusses the analysis of Indonesian language errors in the student’s story telling activities of universitas terbuka (open and distance learning/ODL university in Kefamenanu, north sentral timor regency. The research aims to describe Indonesian language errors in story telling activities. The method applied in this research in qualitative, descriptive, describing or portraying existing phenomena naturally or artificially. Data collection techniques include recording video speeches ODL university students during the story telling activities. Meanwhile, data analysis techniques cover three stages collecting data, identifying data. The results show that Indonesian language errors produced by the students comprise errors in phonology, semantics, and morphology.